Change in 12‐month health care utilization patterns among persons living with dementia who received a comprehensive home‐based dementia care coordination program: Mind at home: Dementia care research (research projects; nonpharmacological)/Community care. (7th December 2020) - Samus, Quincy M; Amjad, Halima; Huang, Jin; Leoutsakos, Jeannie‐Marie S; Lyketsos, Constantine; Johnston, Deirdre
Abstract: Background: MIND at Home, a value‐based innovation, is a comprehensive, home‐based care coordination program for people with dementia and their carers to identify and address a broad set of health determinants to improve health, clinical outcomes, and reduce costs. We present pooled trial data evaluate change in 12‐month health care utilization patterns among a racially and cognitively diverse group of persons living with dementia who received MIND at Home. Method: Pre‐post, adjusted Poisson regression models were used to evaluate health care utilization patterns for a pooled sample of persons with dementia receiving MIND at Home (n=391) in the 12 month period after enrollment in the program with the 12 month period prior to enrollment. Hospitalizations, ED visits, outpatient visits, home and community‐based services (HCBS) were ascertained via proxy‐report from carers. Result: The mean number of hospital admissions decreased by 27% in the one year period after baseline (95% CI: 6%, 44%, p =0.01) compared with the year prior. Adjusted rates of one or more hospitalizations declined from 36.8% to 32.5%, with a crude rate reduction of 11.6% (unadjusted) between pre‐and post‐periods. Mean number of HCBS services used increased by 70% (95% CI: 54%, 88%, p <0.01) and mean number of outpatient specialties seen in the post period increased by 52% (95% CI: 43%, 62%, p <0.01) compared with the year before baseline. Average number of outpatient provider visits remained the same (p=0.76). Mean number of ER visits decreased by 16% (95% CI: ‐8%, 34%) but was not statistically significant ( p =0.18). Conclusion: Results provide compelling new quasi‐experimental data that supports the impact of the MIND at Home program on changing health care utilization patterns and is in line with our prior findings. Persons who received MIND at Home were less likely to use high cost acute health services (inpatient) and more likely to use more cost‐efficient services like home and community based services and physician services in the year after enrollment compared to the year prior. These data imply a potential cost benefit of the MIND at Home dementia care coordination program.